DAKWAH DAN MORALITAS PEMUDA (Analisis Gerakan Dakwah Jamaah Hadrah Nurul Mustofa dalam Membentengi Moral Pemuda) - M. Sofiatul Iman (Universitas Islam Lamongan, 2018)
Abstract: Da'wah messages can be accepted among the (youth) community through da'wah packages that attract the attention of da'wah objects (mad'u). In packing da'wah messages, it is necessary to understand the mad'u situation, as done by jam'iyyah Hadrah Nurul Mustofa, which is much favored by young people, especially in Darungan-Cangkring-Jenggawah-Jember. The da'wah activities carried out by the Hadrah Nurul Mustofa have a special attraction for members and the community in general as their madú. Because the design of the da'wah movement is carried out in balance with the social conditions of young people who incidentally are alcoholic addicts. The purpose of this study is to understand the propaganda movement carried out by the Hadrah Nurul Mustofa to provide academic contributions with a theoretical description in the missionary movement, in addition it also provides a broad understanding for readers regarding the missionary movement, especially for Muslims who have the obligation to convey religious messages through da'wah. In this study, the researcher uses descriptive qualitative methods to explore data. This type of research uses a phenomenological approach that describes the general meaning of a number of individuals on various life experiences, so that the researcher can explore data relating to the tendency of youth and general habits already inherent in their social life. Collecting data in this study with active participant observation, non-structural in-depth interviews so that the data needed can be explored as deeply as possible. Data analysis uses a combined description of the phenomenon being studied by including textural descriptions and structural descriptions. This is the essence of individual experience that is the object of research and displays the peak aspects of phenomenological studies. The validity of the research data uses data triangulation which includes source triangulation, technique triangulation and time triangulation. The conclusion of this research is that the Majlis Shalawat Nurul Mustofa in fortifying youth morality is by using an emotional approach so that they have self-motivation in leaving all the wrong behaviors and doing good deeds or positive attitudes.Keyword: Da'wah, Moral, Youth